2020
DOI: 10.1103/physrevb.101.184406
|View full text |Cite
|
Sign up to set email alerts
|

Spin orbitronics at a topological insulator-semiconductor interface

Abstract: Topological insulators (TIs) hold great promise for new spin-related phenomena and applications thanks to the spin texture of their surface states. However, a versatile platform allowing for the exploitation of these assets is still lacking due to the difficult integration of these materials with the mainstream Si-based technology. Here, we exploit germanium as a substrate for the growth of Bi 2 Se 3 , a prototypical TI. We probe the spin properties of the Bi 2 Se 3 /Ge pristine interface by investigating the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Here, we characterize this additional effect, and we find a solution for correcting the results. Our findings are relevant for experiments where the circularly polarized focused beam is used to probe locally the helicitydependent properties [19][20][21][22][23][24]26,29,31,34 , as the thermal gradients create similar signals. Furthermore, for experiments using a fixed circularly polarized beam 18,25,27,28,30,32,33,[36][37][38] , the beam deflection associated to the helicity reversal may slightly modify the illumination conditions and also influence the results.…”
mentioning
confidence: 75%
See 2 more Smart Citations
“…Here, we characterize this additional effect, and we find a solution for correcting the results. Our findings are relevant for experiments where the circularly polarized focused beam is used to probe locally the helicitydependent properties [19][20][21][22][23][24]26,29,31,34 , as the thermal gradients create similar signals. Furthermore, for experiments using a fixed circularly polarized beam 18,25,27,28,30,32,33,[36][37][38] , the beam deflection associated to the helicity reversal may slightly modify the illumination conditions and also influence the results.…”
mentioning
confidence: 75%
“…It has been shown that circularly polarized 15 light can induce the magnetization reversal 5,16 as well as produce photovoltaic or photoresistive effects 17,18 . The changes of photoresistance [19][20][21][22][23][24][25] or photocurrent 24,[26][27][28][29][30][31][32][33][34][35][36] have been attributed to the interaction between light and spin accumulation. This type of effect appears to be "universal", as it has been observed in semiconductors 24,27 , semimetals 25,37 , topological insulators [29][30][31][32][33][34][35][36] , normal metals 19,20 and even complex metalorganics structure 38 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, we report on the drift-diffusive spin-transport regime in lightly n-doped Ge at room temperature. We exploit the optical orientation technique 28,29 taking place below the edges of Pt stripes [30][31][32] to locally generate spin-polarized electrons in Ge. The spin detection is performed by measuring the voltage drop given by the inverse spin-Hall effect (ISHE) in a thin Pt pad 33,34 grown on Ge and spatially separated from the point where spin is generated.…”
Section: Article Scitationorg/journal/apmmentioning
confidence: 99%
“…21 In addition, a complicated "spin texture" is found at the surfaces of either bulk Bi 18,22,23 or Bi alloys. 24,25 In semi-metallic Bi, spin-related effects involving electron transport are enhanced due to the limited contribution to the electrical conductivity coming from bulk electronic states, making these systems very attractive for applications in the field of spintronics. 26 Spin-resolved photoemission spectroscopy (SR-PES) is the technique of choice to map the electronic structure of Bi surfaces and thin films, being also sensitive to the peculiar spin texture stemming from the presence of SOC effects.…”
Section: Introductionmentioning
confidence: 99%